1989
DOI: 10.1063/1.857555
|View full text |Cite
|
Sign up to set email alerts
|

The delay of turbulent boundary layer separation by oscillatory active control

Abstract: Active control of turbulent boundary layer noise transmission through an aeroelastic plate

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

1991
1991
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(12 citation statements)
references
References 3 publications
1
11
0
Order By: Relevance
“…It should also be noted that a -~45% reduction in Y0 (relative to the unexcited flow) was observed when the flow was excited. Such phenomena were already disclosed by Katz et al (1989).…”
Section: Frequency Response Validity Testmentioning
confidence: 74%
See 1 more Smart Citation
“…It should also be noted that a -~45% reduction in Y0 (relative to the unexcited flow) was observed when the flow was excited. Such phenomena were already disclosed by Katz et al (1989).…”
Section: Frequency Response Validity Testmentioning
confidence: 74%
“…Phase-locked average velocities revealed (Katz et al 1989) that the forcing frequency information is retained throughout the flow field. It was therefore expected that Yo (t) will also exhibit oscillatory motion at the forcing frequency or its sub-harmonics.…”
Section: Frequency Response Validity Testmentioning
confidence: 99%
“…A flat plate case is considered 3 at Re x = U∞ x ν = 4.3 10 8 , at which position the boundary layer has the following characteristics:…”
Section: Interpretation and Usementioning
confidence: 99%
“…The present paper will consider only the case of pulsating jets, although there seems to exist a similarity between these two flow control methods. There exists also ample experimental evidence in the literature, [3,7,18,21], for this kind of flow control. A recent detailed review is provided in [2] mentioned above.…”
Section: Introductionmentioning
confidence: 96%
“…Reynolds and Carr (1985) interpreted the findings of Francis et al from a viewpoint of vorticity dynamics. Recently, Katz et al (1989) reported that by installing an oscillating plate at the apex of a wedge, the original separated flow could be suppressed by the introduction of two-dimensional small-amplitude perturbation. Koga (1983), Reisenthel et al (1985) and Nagib et al (1985) have shown that by installing an oscillating flap in the separated region behind a backward-facing step the reattachment length could be reduced by up to 60%.…”
Section: Introductionmentioning
confidence: 99%